An Evo-Devo Approach to Thyroid Hormones in Cerebral and Cerebellar Cortical Development: Etiological Implications for Autism - Berbel, Pere; Navarro, Daniela; Román, Gustavo C. (Frontiers in Endocrinology, 2014)
The morphological alterations of cortical lamination observed in mouse models of developmental hypothyroidism prompted the recognition that these experimental changes resembled the brain lesions of children with autism; this led to recent studies showing that maternal thyroid hormone deficiency increases fourfold the risk of ASD, offering for the first time the possibility of prevention of some forms of autism spectrum disorders (ASD). For ethical reasons, the role of thyroid hormones on brain development is currently studied using animal models, usually mice and rats. Although mammals have in common many basic developmental principles regulating brain development, as well as fundamental basic mechanisms that are controlled by similar metabolic pathway activated genes, there are also important differences. For instance, the rodent cerebral cortex is basically a primary cortex, whereas the primary sensory areas in humans account for a very small surface in the cerebral cortex when compared to the associative and frontal areas that are more extensive. Associative and frontal areas in humans are involved in many neurological disorders, including ASD, attention deficit-hyperactive disorder (ADHD) and dyslexia, among others. Therefore, an evo-devo approach to neocortical evolution among species is fundamental to understand not only the role of thyroid hormones and environmental thyroid disruptors on evolution, development and organization of the cerebral cortex in mammals, but also their role in neurological diseases associated to thyroid dysfunction.